Membangun Kemandirian Ekonomi Lokal Masyarakat Desa melalui Pemberdayaan Usaha Bersama Komunitas (UBK) - Mala, Istana Wijayanti; Misnan; Setianingsih S, Endang (Universitas Dr. Soetomo Surabaya, 2024)
One form of poverty reduction empowerment is in the form of community-based community businesses that are carried out by establishing Community Joint Ventures such as those carried out by the Ngale Village Government. This research aims to comprehensively analyze how the implementation of the development of local economic independence of village communities through the empowerment of Community Joint Ventures. This research was conducted using a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation. Data analysis was carried out through interactive analysis techniques based on empowerment indicators which include: enabling, strengthening, protecting, and supporting. The results show that community empowerment through Community Joint Ventures in Ngale Village has been going on quite well, but not optimally. Enabling is quite effective because the empowerment process is done from the bottom up. Strengthening is already underway, but it is still limited to production. Protection is already in place but is less than optimal because it is only in the form of institutional legitimization and capital assistance. Only support that runs optimally because there is direct government support and participation. However, the Ngale Village Community Joint Venture has succeeded in building the economic independence of the village community when looking at the fulfillment of living needs, changes in household life, and psychological changes in family members